Benefit administration of vitamin B1, B6, and B12 on the depression symptom in hemodialysis patients - Rizaldy Taslim Pinzon; Birgitta Lisbethiara Ardiani (Universitas Muhammadiyah Malang, 2019)
Chronic kidney disease (CKD) is a disease that causes a decrease in kidney function, which can be seen from GFR (Glomerulus Filtration Rate) value, which is less than 60 ml/minute/1.73 m2 in minimum three months. Depression is a psychological problem in a patient with chronic kidney disease undergoing hemodialysis. The previous study has shown that giving vitamin B combination can improve depression symptoms. To measure the benefit of vitamin B1, B6, B12 parenterally for depression symptoms in chronic kidney disease patients undergoing hemodialysis. This study used an experimental design (one group pre and post-test) in 117 patient that obtained using a consecutive sampling method. Depression score was measured by the HADS questionnaire before given vitamin B (pre-test) and after given vitamin B (post-test). Data were statistically analyzed using a licensed SPSS program with paired t-test/Non-Parametric Wilcoxon. The relationship between the history of the use of the antihypertensive, antidiabetic, folic acid drug, and depression scores were not showing significant results (p > 0.05). The relationship between administration of vitamins B1, B6, and B12 and the patient's depression score showed a decrease but not significant (p = 0.522). There was no significant difference after the administration of vitamin B1, B6, and B12 on the depression score of patients with chronic kidney disease undergoing hemodialysis at Bethesda and Panti Rapih Hospital in Yogyakarta.